2018
DOI: 10.12659/msm.910316
|View full text |Cite
|
Sign up to set email alerts
|

miR-155-5p Promotes Progression of Acute Respiratory Distress Syndrome by Inhibiting Differentiation of Bone Marrow Mesenchymal Stem Cells to Alveolar Type II Epithelial Cells

Abstract: BackgroundWe investigated whether microRNA-155-5p is involved in the differentiation of bone marrow mesenchymal stem cells (BMSCs) into alveolar type II epithelial (AT II) cells by regulating the Wnt signaling pathway, thus participating in the development of acute respiratory distress syndrome (ARDS).Material/MethodsSerum levels of microRNA-155-5p in 50 ARDS patients and 50 normal controls were detected by quantitative real-time PCR (qRT-PCR). Marrow mesenchymal stem cells (MCSs) were isolated from mouse bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…MiR-155 plays crucial roles in the immune response, tumorigenesis and stem cell differentiation [33][34][35][36] and has been reported to target and repress many genes including SOCS1, TNF-α, and SHIP1 [18][19][20]. Dudda et al reported that miR-155 and its target gene, SOCS1, are key regulators of effector CD8( +) T cells as they affect cytokine signaling through STAT5 [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-155 plays crucial roles in the immune response, tumorigenesis and stem cell differentiation [33][34][35][36] and has been reported to target and repress many genes including SOCS1, TNF-α, and SHIP1 [18][19][20]. Dudda et al reported that miR-155 and its target gene, SOCS1, are key regulators of effector CD8( +) T cells as they affect cytokine signaling through STAT5 [37].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-155 plays crucial roles in the immune response, tumorigenesis and stem cell differentiation [ 33 – 36 ] and has been reported to target and repress many genes including SOCS1, TNF-α, and SHIP1 [ 18 20 ]. Dudda et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several immunomodulatory factors, released during ARDS, may reduce differentiation of MSCs into ATII-like cells and consequently attenuate therapeutic potential of MSCs in the treatment of ARDS. Overexpressed microRNA-615-3p or microRNA-155-5p inhibits differentiation of MSCs into ATII cells leading to the progression of ARDS [37, 38]. Pathological changes in the microenvironment of ARDS-injured lungs, in turn, negatively affect the capacity of MSCs to proliferate and differentiate into ATII cells [39].…”
Section: Msc-mediated Attenuation Of Ards and Pneumoniamentioning
confidence: 99%
“…MiRNAs are present in the circulatory system and changes in miRNA expression may herald the development of a variety of diseases including ALI (22,23). Cardinal-Fernández et al (24) have proposed that miRNAs are suitable biomarkers and therapeutic targets for ALI.…”
Section: Discussionmentioning
confidence: 99%